Surgical atlas of sports orthopaedics and sports traumatology - Imhoff, Andreas B.; Feucht, Matthias J.; Aboalata, Mohamed; Aboalata, Mohamed (Springer, 2015)
This atlas depicts and describes the newest arthroscopic and open techniques for dealing with sports orthopaedic injuries and problems. More than 75 surgical procedures are presented step by step with the aid of superb illustrations. Arthroscopic views, artist drawings, X-rays, and clinical and operative photographs are all included to demonstrate exactly how each procedure should be performed.